1995
DOI: 10.1007/bf01143138
|View full text |Cite
|
Sign up to set email alerts
|

Data compression of X-ray cardio-angiographic image series

Abstract: Medical x-ray images are increasingly stored and transmitted in a digital format. To reduce the required storage space and transmission bandwidth, data compression can be applied. In this paper we describe a new method for data compression of cardio-angiographic x-ray image series. The method is based on so-called overlapped-transform coding. A comparison with the well-known block-based transform-coding methods JPEG and MPEG is presented. We found that overlapped-transform coding does not introduce any blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Unfortunately, this approach is not acceptable for functional neuroimaging, as it does not properly handle changes in head position during the scan series. Finally, it is worth noting that publicly available lossy compression systems such as MPEG and JPEG are unsuitable for quantitative statistical analyses as commonly performed for functional imaging studies [Breeuwer et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this approach is not acceptable for functional neuroimaging, as it does not properly handle changes in head position during the scan series. Finally, it is worth noting that publicly available lossy compression systems such as MPEG and JPEG are unsuitable for quantitative statistical analyses as commonly performed for functional imaging studies [Breeuwer et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that no statistically significant loss of diagnostic quality was detected for 8 or 7-bit compress images with average compression ratios of 16:1 and 28:1 [11] . In 1995, Breeuwer et al [12] discussed the diagnostic consequences of compression using cosine transform. They reported that acceptable compression ratio for image size of 2048, 1024 and 512 pixels were 25:1, 20:1 and 10:1 respectively based on a mean square error of 0.02%.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…They reported that acceptable compression ratio for image size of 2048, 1024 and 512 pixels were 25:1, 20:1 and 10:1 respectively based on a mean square error of 0.02%. The researchers concluded that reconstructed images from compressed image data with a compression ratio of 4:1-16:1 did not result in excessive visual degradation and therefore this technique was suitable for compression of diagnostic images [12] . In 1997, Erickson et al [13] found that a lossy compression of 40:1 or more could be used without perceptible loss in the representation of anatomical structures.…”
Section: Review Of Related Workmentioning
confidence: 99%